Early Warning System, Solusi Digital Mitigasi Risiko Dalam Transformasi Integrasi Layanan Kesehatan Primer - Kori Puspita Ningsih; Choerun Asnawi; Heri Hernawan; Angga Eko Pramono; Nur Rokhman (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Integration of Primary Health Services is a priority program in primary health care facilities to support health transformation in Indonesia. The priority issues at community health centers (Puskesmas) within the Bantul Health Office area include a lack of understanding among health workers regarding health service risk management, and the use of manual forms for risk management reporting, which does not utilize information technology. Risk management plays a crucial role in preventing program failure, particularly in the implementation of Integration of Primary Health Services at Bantul Community Health Centers, which began in 2024. The Community Service (PKM) activities comprised risk management training and the dissemination of research results for a prototype risk mitigation calculator application based on an Early Warning System (EWS) dashboard, conducted through lectures, practical exercises, and discussions. Overall, the PKM implementation proceeded smoothly and in an orderly manner. The pre-test and post-test results of 27 participants showed an increase in the level of community empowerment in the knowledge aspect with an average score of 21, where the average initial score of 69.9 during the pre-test increased to 90.9 during the post-test. Participants were also able to simulate the use of the application, including installation, data input, output interpretation, and form printing, according to their respective access levels. Through this increased empowerment of partners, it is expected that Bantul community health centers will be able to properly document their risk management processes, which will enable the optimal implementation of the Integration of Primary Health Care program.